منتج المرابحة بالذهب في البنك الحكومي الإندونيسي الإسلامي: دراسة تحليلية وتقويمية - مارضيانا (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The term of Murabaha (murabahah), and gold investment are among the most important topics nowadays due to the massive dealing with them among many people in the society. Therefore, this research is an attempt to merge these two issues into one transaction which is called “Gold Murabahah”. The concepts of both Murabahah and Goldand their applications in by Indonesian Government Islamic Bank have been given special attention to fiqh issues related to the application and its provisions, to determine wheter it is syari'ah compliant or not. To achieve the objectives of this research, the methodologies based on the inductive approach and analytical exploration of texts and researches related to the topic to gather the views of Muslim scholars, researchers, and their evidence and arguments on the matter. This is followed by analysis, discussion and highligh of the predominant opinion. Moreover, the field study that was conducted in the Government Indonesian Islamic Bank was used to link between the theoretical and the practical side. In summary,the application ofGold Murabahah in The Indonesian Government Islamic Bank, needs to be revised, to the make gold as Usul Murabaha. It has been concluded that ribawi item requires uniformity and trading at the exact same time, involved delayed payment of the gold price which considered riba. Finally, the research proposed some solutions to this process for the transaction to be free of prohibited elements.